The Pattern of Prostate Cancer Screening and Diagnosis among Indonesian Urologists: A Questionnaire Survey - Muhammad Firman; Fakhri Rahman; Agus Rizal Ardy Hariandy Hamid; Chaidir Arif Mochtar (Indonesian Journal of Cancer, 2023)
Background: Prostate cancer (PCa) screening and diagnosis are mandatory to deliver optimal management in the early phase. Even though it has been discussed in many guidelines, the implementation of PCa screening and diagnosis in Indonesia remains unknown. This study aims to evaluate the pattern of PCa screening and diagnosis among Indonesian urologists and their adherence to guidelines. Methods: This cross-sectional study was conducted between February and July 2019. Respondents were Indonesian urologists registered as members of the Indonesian Urological Association (IUA) and had already practiced for at least six months. Data were collected using questionnaires, which were distributed at a national urology symposium and electronically via Google Form. Data were presented descriptively, and all data were processed using SPSS version 23. Results: Of 458 urologists, 195 (42.6%) gave full responses. Most of the respondents, 181 (92.8%) urologists, used the IUA guidelines. Among the 103 (52.8%) respondents who performed screening, nearly half (42.7%) agreed to screen patients aged ≥ 50 years or ≥ 45 years with a family history of PCa. Moreover, 76.8% would repeat screening annually, and 35.6% would stop when the patient’s age reached 70 years old. Digital rectal examination (DRE) was frequently performed for screening (74.5%), while prostate-specific antigen (PSA) tests were only performed in 52.3% of cases. The PSA test was available in 74.8% of hospitals. Transurethral resection of the prostate (TURP) was still used by 67.2% of respondents for diagnosis. Only 52.3 % of participants used transrectal prostate biopsy for diagnosis, using anesthesia (78.1%) during the procedure, and increased PSA level (98%) as its indication. However, Transrectal Ultrasound (TRUS) was only available in 49% of hospitals. This study found that Indonesian urologist adherence level toward guidelines was 63.3% (9–100%). Conclusions: PCa screening and diagnosis are still varied among Indonesian urologists, which might arise due to the different availability of diagnostic modalities.